COMPARISON OF SCIENCE SCIENCES PROGRAMS: TURKEY AND SINGAPORE - Mürşide KILIÇ; Hikmet SÜRMELİ (International Journal of Eurasia Social Sciences, 2017)
In this study, the science curriculum in Turkey and the science curriculum in Singapore was compared in terms of objectives and contents. Document analysis was used while analyzing the objectives and content of the both science curriculums as a qualitative research method. In this research, purposes, visions, units and learning areas of the both curriculum were compared. In addition, distribution of learning areas, units and learning achievements were compared in terms of class levels and similarities and differences were tried to revealed. Results of this study showed that the objectives of science curriculum applied in Turkey were more detailed than the science curriculum applied in Singapore. In both curriculum, the units were arranged in spiral structure. Considering class level, It was also found that the number of learning achievements were more in science curriculum applied in Turkey comparing science curriculum applied in Singapore. In addition, Singapore science curriculum aims to teach their students skills related to their close environments, whereas the science curriculum of Turkey aims to teach the combination of close environment and remote environment skills. The science curriculum in Turkey and the science curriculum in Singapore seem to be similar to each other in terms of the skills and skills they want to have in their individuals. Recommendations were made in the kşght of these results.